2008
DOI: 10.1016/j.cellbi.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin extrusion in resting encystment of Colpoda cucullus: A possible involvement of apoptosis‐like nuclear death

Abstract: The extrusion of macronuclear chromatin is a remarkable characteristic during encystment in Colpoda, but the biological significance of this phenomenon has not been fully elucidated. Here we demonstrate that chromatin extrusion occurs with high frequency when encystment was induced by increasing Ca(2+) in growing cells in various stages of the cell cycle. The Feulgen-DNA reaction revealed that vegetatively growing cells have more macronuclear DNA than cells in the stationary phase, suggesting an association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…), and thereafter a large mass of chromatin is often extruded from the macronucleus (Kidder and Claff ). The extruded chromatin mass is degraded by autophagy for 1–2 d (Akematsu and Matsuoka ; Funatani et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), and thereafter a large mass of chromatin is often extruded from the macronucleus (Kidder and Claff ). The extruded chromatin mass is degraded by autophagy for 1–2 d (Akematsu and Matsuoka ; Funatani et al. ).…”
mentioning
confidence: 99%
“…In 2-3 h after the onset of encystment induction, many small chromatin granules are extruded from the macronucleus to be digested in the cytoplasm (Funatani et al 2010), and thereafter a large mass of chromatin is often extruded from the macronucleus (Kidder and Claff 1938). The extruded chromatin mass is degraded by autophagy for 1-2 d (Akematsu and Matsuoka 2008;Funatani et al 2010). Mitochondrial membrane potential disappears in 7-15 h after the onset of encystment induction (Funatani et al 2010).…”
mentioning
confidence: 99%
“…Therefore, AIF may be bifunctional, serving as both a vital protein and a death effector. Among ciliates, apoptosis-like nuclear degradation has been observed during resting cyst formation leading to change in macronuclear DNA content in Colpoda [29]. In this case, the macronuclear chromatin is extruded into the cytosol, and the degradation of the extrusion body is accompanied by a reduction in the size of the nucleus, oligonucleosome-size DNA cleavage, and nuclear acidification by lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The vegetative cells of C. cucullus cultured in a cereal (wheat leaves) infusion containing bacteria have been shown to grow rapidly for 1-1.5 days; thereafter, the cells begin to encyst (spontaneous encystment) [8]. Our preliminary observation showed that it was difficult to induce rapidly growing cells to encyst, while post-growing cells were apt to encyst.…”
Section: Introductionmentioning
confidence: 72%